Morphological and initial molecular characterization of Clogmia albipunctatus larvae (Diptera: Psychodidae) causing urinary myiasis in Egypt. - Haiam Mohammed Mahmoud Farrag; Enas Abdelhameed Mahmoud Huseein; Amal M Almatary; Ragaa A Othman (PLoS Neglected Tropical Diseases, 2019)
Myiasis is the infestation of human tissues by dipterous fly larvae of the class Insecta. Clogmia albipunctatus, family Psychodidae, is one of the most medically important insects that cause human myiasis. The aim of the present study is the morphological identification and the molecular characterization of moth flies causing many cases of urinary myiasis in Egypt, based on sequencing of the mitochondrial DNA of the larvae. Seven urinary samples of patients complaining of urinary symptoms and giving a history of low socioeconomic level were examined. Recovered larvae were identified using light microscopy and SEM. For molecular identification, the mitochondrial genes Cytochrome B (cytB), NADH1, NADH1, and 16S were sequenced and phylogenetically analyzed. The morphological and molecular characterization could accurately diagnose our patients to have C. albipunctatus infestation. Such results provided the initial set of data on the molecular identification and phylogenetic analysis of moth flies based on DNA barcoding in Egypt.